IMPLEMENTASI PRINSIP PARETO PADA PEKERJAAN PERBAIKAN DI PROYEK PERUMAHAN: STUDI KASUS: PROYEK PERUMAHAN DI KOTA TANGERANG SELATAN - Irfanto, Ryobi; Charolin, Eva (Universitas Trisakti, 2024)
Rework in construction refers to the activity of repairing or redoing work that does not meet quality standards, causing delays and increased costs. The aim of this research is to identify the causes of rework in building structures, with a case study of four types of houses in one of the housing complexes in South Tangerang City. This research focuses on the use of quality improvement tools such as Pareto Charts. Pareto diagrams, based on the Pareto principle which states that most consequences come from a small number of causes, are used to identify and prioritize the causes of rework. The types of work that most frequently result in rework will be monitored more closely to minimize future errors. Data collection through field observations by calculating the frequency of repair work. The results of the analysis show that most rework is caused by some type of repeated error. The implementation of Pareto resulted in 75% of rework resulting from 50% of the causes. There were 5 causes of rework occurring which were analyzed, namely inappropriate dimensions, elevation differences, slanted formwork, ends of reinforcement that were not connected, and reinforcement that needed cleaning. This implementation helps in solving these 5 problems and provides lessons for other similar projects